2017
DOI: 10.1080/13607863.2017.1373065
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement of the international summit on intellectual disability and Dementia related to post-diagnostic support

Abstract: Objectives: Post diagnostic support (PDS) has varied definitions within mainstream dementia services and different health and social care organizations, encompassing a range of supports that are offered to adults once diagnosed with dementia until death. Method: An international summit on intellectual disability and dementia held in Glasgow, Scotland in 2016 identified how PDS applies to adults with an intellectual disability and dementia. The Summit proposed a model that encompassed seven focal areas: post-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
(39 reference statements)
1
19
0
1
Order By: Relevance
“…The perspective pharmacological interventions in the sub-group of MCI cases whose deterioration is anticipated [ 2 , 181 ] could be beneficial in alleviating appetite/eating disturbances and providing tailored solutions, due to the divergent actions of ACHEIs [ 164 , 165 , 166 , 167 ]. The NMDA antagonist memantine has been also reported capable to mitigate overall NPI prevalence in combined schemes with donepezil, and especially up to 4.8 points in replacement schemes [ 182 ], with significant improvement of the appetite/eating cluster, possibly due to the normalization of binge-eating [ 183 ].…”
Section: The Emerging Role Of Salience Network In Appetite Regulamentioning
confidence: 99%
See 2 more Smart Citations
“…The perspective pharmacological interventions in the sub-group of MCI cases whose deterioration is anticipated [ 2 , 181 ] could be beneficial in alleviating appetite/eating disturbances and providing tailored solutions, due to the divergent actions of ACHEIs [ 164 , 165 , 166 , 167 ]. The NMDA antagonist memantine has been also reported capable to mitigate overall NPI prevalence in combined schemes with donepezil, and especially up to 4.8 points in replacement schemes [ 182 ], with significant improvement of the appetite/eating cluster, possibly due to the normalization of binge-eating [ 183 ].…”
Section: The Emerging Role Of Salience Network In Appetite Regulamentioning
confidence: 99%
“…The NMDA antagonist memantine has been also reported capable to mitigate overall NPI prevalence in combined schemes with donepezil, and especially up to 4.8 points in replacement schemes [ 182 ], with significant improvement of the appetite/eating cluster, possibly due to the normalization of binge-eating [ 183 ]. The parallel actions against the BPSD array are fortunate [ 184 ], as only timely use of anti-dementia medication is suggested at the moment [ 2 ]. However, with the exception of rivastigmine, little evidence exists about the pathways implicated in appetite regulation during these interventions.…”
Section: The Emerging Role Of Salience Network In Appetite Regulamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are four published studies and Cochrane reviews that show no benefit with donepezil, 2 rivastigmine, 3 memantine, 4,5 or galantamine. 6 Another Cochrane Review in 2015 showed no benefit of pharmacological interventions for cognitive decline in people with Down syndrome.…”
mentioning
confidence: 99%
“…It is important not to overlook dementia as an early diagnosis can facilitate prompt pharmacological and psychosocial treatments and effective care planning. 5 When dementia is diagnosed, a decision to use medication is, of course, an individual one, and should take account of the views of families and carers. Our paper provides additional evidence that could inform the decision-making process.…”
mentioning
confidence: 99%